Dimensi Shalat dalam Kehidupan Spiritual dan Sosial - Kuni Kyla Afifah; Khaila Dila Salwa; Daffa Al Dzaki; Andryani Andryani; Ayunda Larasati Sekarputri (Karakter : Jurnal Riset Ilmu Pendidikan Islam, 2026)
In the contemporary era,many people have yet to fully comprehend or internalize the spiritual and social dimensions of prayer (shalat). As a result, shalat is often carried out merely as a routine obligation without deep reflection on its true purpose. In fact, shalat plays a significant role in shaping personal character and social behavior. This study employs a literature review approach by examining various sources, including books, academic journals, and educational articles that discuss the concept and significance of shalat as an act of worship. The findings indicate that a profound understanding of the inner meanings of shalat can foster self-awareness, self-control, and discipline. These values strongly contribute to the development of moral and ethical character. Furthermore, shalat reflects collective religiosity through its practices and procedures, symbolizing spiritual purification, reverence for God, and awareness of human limitations. Congregational prayer further emphasizes principles of unity, brotherhood, and equality, regardless of social status or background. In addition, shalat functions as a moral safeguard that prevents individuals from engaging in immoral and harmful actions. Therefore, shalat plays a crucial role not only in strengthening spiritual devotion but also in maintaining personal integrity and social harmony.